Uncovering the role of the Hsp40 family member cysteine string protein-α in mouse platelets - Alexis N. Smith; Hammodah R. Alfar; Smita Joshi; Daniëlle M. Coenen; Joshua Lykins; Isabelle C. Becker; Brittany E. Dong; Harry Chanzu; Chi Peng; Kanakanagavalli Shravani Prakhya; Linda Omali; Irina D. Pokrovskaya; et al. (Blood Advances)
Abstract: Platelets modulate vascular microenvironments via the release of cargo molecules. Granule secretion is modulated by proteins called soluble N-ethylmaleimide sensitive factor attachment protein receptors (SNAREs). Secretion is complex and regulated by several protein-protein interactions; however, not all are characterized in platelets. We have identified cysteine string protein-α (CSPα; also known as, DNAJC5 or CLN4) as required for platelet secretion. CSPα is the only member from the CSP family present in platelets and has been proposed as a chaperone for the SNAP-23/25 t (Qb,c) SNAREs. To address CSPα’s role, we analyzed platelets from CSPα−/− mice. The loss of CSPα significantly affected dense- and α-granule release with minimal effects on lysosomal secretion. Consistent with the secretion defects, in vivo and ex vivo assays showed that loss of CSPα caused significant bleeding and attenuated thrombosis under flow. Interestingly, loss of CSPα caused a reduction in glycoprotein VI (GPVI) levels and reduced αIIbβ3 activation, especially in response to GPVI-specific agonists. Deletion of CSPα did not affect proteins in the platelet secretory machinery, for example, the SNAP-23/25 proteins. Subcellular fractionation studies showed that CSPα, which is reported to be acylated, was present on membranes but not in lipid rafts. Immunofluorescence studies showed CSPα colocalized with α and lysosomal granule markers. CSPα−/− mice had reduced red blood cell, leukocyte, and megakaryocyte numbers, suggesting effects on bone marrow progenitor cells. Simultaneously, we detected increased collagen I deposition, but no fibrosis in the marrow of CSPα−/− mice. These results identify CSPα as another element of the platelet secretory machinery that significantly contributes to thrombosis and hemostasis.